2017
DOI: 10.1002/slct.201700334
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Recyclable Metal Salt Catalyst for the Production of Biodiesel: Toward Greener Process

Abstract: A highly reactive and recyclable metal catalyst was reported for the transesterification of model vegetable oil with methanol to produce fatty acid methyl esters (FAMEs) under microwave condition. Among the screened catalysts, Al2(SO4)3 provided the highest FAME yield of 98.1 % at 130 oC within 30 min. Different reaction parameters were fully investigated which were found to have great influences on the product yields. Microwave energy showed a remarkable accelerated reaction rate as compared to that from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…As presented in Figure , a sharp peak at 0.5 ppm was observed immediately after the introduction of Al 2 (SO 4 ) 3 to the D 2 O solvent, which was assigned to the formation of hexa‐coordinated Al species . Furthermore, a weak resonance peak at −2.8 ppm was also observed, which was attributed to the partial coordination of SO 4 2− instead of D 2 O, which shielded the Al center . As the hydrolysis reaction proceeded, the resonance peak center at 0.5 ppm remained unchanged, which indicated that the Al center was in the hexa‐coordinated form throughout the reaction.…”
Section: Resultsmentioning
confidence: 93%
“…As presented in Figure , a sharp peak at 0.5 ppm was observed immediately after the introduction of Al 2 (SO 4 ) 3 to the D 2 O solvent, which was assigned to the formation of hexa‐coordinated Al species . Furthermore, a weak resonance peak at −2.8 ppm was also observed, which was attributed to the partial coordination of SO 4 2− instead of D 2 O, which shielded the Al center . As the hydrolysis reaction proceeded, the resonance peak center at 0.5 ppm remained unchanged, which indicated that the Al center was in the hexa‐coordinated form throughout the reaction.…”
Section: Resultsmentioning
confidence: 93%
“…For the biodiesel production some heterogeneous catalysts have been tested, [7–9] and the alkaline metal oxides like BaO, CaO, MgO, and SrO have proven to be efficient due to their basicity, low activation temperature, and shorter reaction times [10,11] . From these groups of metal oxides, magnesium oxide has attracted the attention of the scientific community, due to its considerable basicity, stability, and not dissolution in the reaction medium [12,13] …”
Section: Introductionmentioning
confidence: 99%
“…[5] In this respect, biodiesel can be used as a green replacement for Petro diesel due to its low sulfur content, no harmful aromatics, improved combustion (10-11 % of oxygen content), higher flash point, inherent lubricity, and reduced carbon dioxide emissions. [6] For the biodiesel production some heterogeneous catalysts have been tested, [7][8][9] and the alkaline metal oxides like BaO, CaO, MgO, and SrO have proven to be efficient due to their basicity, low activation temperature, and shorter reaction times. [10,11] From these groups of metal oxides, magnesium oxide has attracted the attention of the scientific community, due to its considerable basicity, stability, and not dissolution in the reaction medium.…”
Section: Introductionmentioning
confidence: 99%
“…30,32 Because of these benefits, MW could be a potential technique for promoting esterification reactions. 33 Although MW has been extensively used as an assisted technique in catalytic organic synthesis, [34][35][36][37][38] no study has reported its use in the noncatalytic esterification of levulinic acid. Noncatalytic levulinic acid esterification with ethanol using MW can facilitate an energy-efficient and ecofriendly process for preparing ethyl levulinate.…”
Section: Introductionmentioning
confidence: 99%